Restriction fragment length polymorphism-based genotyping of Toxoplasma gondii from autopsy-proven cases of acquired immunodeficiency syndrome-associated cerebral toxoplasmosis - Vijaykumar, B; Kant, R; Rajendran, C; Lekshmi, Swathi; Keerthana, Sundar; Mahadevan, Anita; Shankar, S; Jayshree, R (Annals of the Indian Academy of Neurology, 2018)
Context: Published data on genetic characterization of Toxoplasma gondii (T.gondii) from clinical cases of toxoplasmosis from India is lacking. Aims: The present study was aimed at identifying genetic types of T. gondii in fatal cases of cerebral toxoplasmosis (CT) associated with HIV, from India. Settings and Design: Archived tissues of CT were obtained postmortem from 25 acquired immunodeficiency syndrome patients between 2000 and 2014. Subjects and Methods: Direct amplification of eight different loci, namely, SAG1, 5'-3'SAG2, Alt. SAG2, SAG3, BTUB, GRA6, C22-8, and L358 followed by restriction fragment length polymorphism was used to genotype the parasite. Results: The canonical Types I, II, or III were not found in our study. More than 96% of the cases harbored atypical genotypes-likely recombinants of the canonical types; one case closely corresponded to Type II genotype. Conclusions: Thus, a majority of T. gondii causing CT in South India belonged to a noncanonical lineage. These nonarchetypal genotypes differed from the conventional Types I, II, and III and caused devastating severity in patients with CT in the background of HIV. These results are a step further to deciphering the population genetics of this important zoonotic parasitic infection in Indian patients, information that has thus far been lacking.